"Everything you ever hoped for" : bld nummer 0. - Michiels, Steve; Peeters, Jan; Lambrecht, Wim; Luyckx, Daphné; Smolders, Lore; Tavernier, Jonas; Vandenabeele, Isabelle; Vandewalle, Dominiq; Sint-Lucas, Gent (Gent : Sint-Lucas Beeldende Kunst, 2009)
Vandenbroucke, Brecht ; Dewanckel, Goele ; Van Dijck, Hannelore ; Vyncke, rein ; Diepens, Carina ; Wolkman, Wesley ; Hudréaux, Céline ; Pevernagie, Renée ; Van Steelandt, Anton ; Willems, Freek ; et al.
boek